Fungsi “Fukugoudoushi –Te Iru” Dalam Novel Jiorama Karya Natsuo Kirino - Indah Apriani; Rudi Hartono Manurung (Bina Nusantara University, 2011)
Japanese is a language that comprises a unique grammar. Internal structure is its uniqueness and can be studied like syntax. One study of Japanese language syntax is functions of “fukugoudoushi” 「て いる」. This theme was chosen to understand the whole functions of “fukugoudoushi” 「ている」. As the corpus of data, a Natsuo Kirino’s novel Jiorama is used. This study implements descriptive analytical method and literature review. From the results obtained, it is concluded that fukugoudoushi